Immigration The Labor Market Effects of a Guest Worker Program for U.S. Farmers. ([s.n.], 2004)
Examines theoretical and estimated empirical effects of temporary alien farm worker programs on wage and job opportunities of domestic farm workers. Reviews arguments for and against such programs and resulting policy issues.